Rational Design of a Robust Fluorescent Probe for the Detection of Endogenous Carbon Monoxide in Living Zebrafish Embryos and Mouse Tissue. Issue 43 (6th October 2017) - Liu, Keyin; Kong, Xiuqi; Ma, Yanyan; Lin, Weiying
Abstract: Carbon monoxide (CO) is one of the most important gaseous signal molecules in biological systems. However, the investigation of the functions of CO in living organisms is restricted by the lack of functional molecular tools. To address this critical challenge, we present herein the rational design, synthesis, and in vivo imaging studies of a powerful two‐photon excited near‐infrared fluorescent probe (1‐Ac ) for endogenous CO monitoring. The advantageous features of the new probe include high stability, low background fluorescence, large fluorescence enhancement, high sensitivity, and two‐photon excitation with emission in the near‐infrared region. Significantly, these merits of the probe enable the tracking of endogenous CO in zebrafish embryos and mouse tissues for the first time. Abstract : CO sensing in vivo : A unique Pd II ‐based two‐photon‐excited near‐infrared fluorescent probe for endogenous CO was rationally designed and constructed. The robust probe exhibited superior properties, which allow the tracking of endogenous CO in zebrafish embryos and mouse tissues for the first time.